The STOP-BANG questionnaire as a screening tool for obstructive sleep apneainduced hypertension in Asian population - Tanut Pavarangkul; Thipphailin Jungtrakul; Pichsinee Chaobangprom; Luxanawadee Nitiwatthana; Wisit Jongkumchok; Weerachat Morrakotkhiew; Sitthan Kachenchart; Jarin Chindaprasirt; Panita Limpawattana; Sompong Srisaenpang; Somdej Pinitsoontorn; Kittisak Sawanyawisuth (MDPI AG, 2016)
Obstructive sleep apnea (OSA) is a common public health issue. If left untreated, OSA may cause a large health economic burden from cardiovascular complications particularly stroke. The diagnosis of OSA can be made by polysomnography, but its availability is limited in the developing countries in Asia. STOP-BANG questionnaire is a good screening tool but may need some adjustment for Asian population. STOP-BANG stands for: Snoring history, Tired during the day, Observed stop breathing while sleep, High blood pressure, body mass index (BMI) more than 35 kg/m2, Age more than 50 years, Neck circumference more than 40 cm and male Gender. We compared clinical features in STOP-BANG questionnaire between 42 OSA induced hypertension patients and 82 healthy control subjects in the Faculty of Medicine, Khon Kaen University, Thailand. The best cutoff point for the BMI and the neck circumference were 24.5 kg/m2 and 36 cm, respectively. The sensitivity and specificity of the BMI cutoff point were 97.2% and 91.40, while those of the neck circumference were 94.7% and 82.9%. In conclusion, the appropriate cutoff points of BMI and neck circumference for Thai STOP-BANG questionnaire were 25 kg/m2 and 36 cm.